Takhlil Al Akhtâ Al Syafawiyyah ‘Inda Al Muhadatsah Al Yaumiyyah Ladâ Tullâb Al Mustawa Al Awwal Min Qismi Al KulliyyahTakhlil Al Akhtâ Al Syafawiyyah ‘Inda Al Muhadatsah Al Yaumiyyah Ladâ Tullâb Al Mustawa Al Awwal Min Qismi Al Kulliyyah: تحليل الأخطاء الشفوية عند المحادثة اليومية لدى طلاب المستوى الأول من قسم الكلية بجامعة الراية - Abdul Fatah (Ukazh : Journal of Arabic Studies, 2025)
This study aims to find out the oral linguistic errors in daily conversation among female students of the Institut Muslim Cendikia in the first semester of the academic year 2025-2026 AD, and how to respond to these errors so that students do not fall into the same mistakes. In writing this study, researchers used descriptive and analytical qualitative methods. And the three ways used by researchers to collect data are: interviews, observation, and documentation. And the results of this study are that oral linguistic errors in daily conversation among female students of the Institut Muslim Cendikia in the first semester of 2025-2026 AD consist of: Errors in the addition of sentences that do not exist in Arabic, , Translation of sentences from Indonesian to Arabic that do not comply with the rules, errors in the use of jar letters, Mad errors in Arabic conversation, errors in the mention of Arabic lafadz, errors in the use of Arabic mufradat, innappriate use of qawaid or grammar.